2006
DOI: 10.1158/1535-7163.mct-06-0316
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of radiation sensitivity in breast tumor cells by the vitamin D3 analogue, EB 1089, through promotion of autophagy and interference with proliferative recovery

Abstract: Abstract1,25-Dihydroxyvitamin D 3 and vitamin D 3 analogues, such as EB 1089, potentiate the response to ionizing radiation in breast tumor cells. The current studies address the basis for this interaction by evaluating DNA damage and repair, the effect of interference with reactive oxygen generation, the involvement of p53 and caspase-3, signaling through c-myc, as well as the induction of senescence and multiple modes of cell death. EB 1089 failed to increase the extent of radiation-induced DNA damage or to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 42 publications
8
60
0
Order By: Relevance
“…2,17 In contrast, treatment with the vitamin D analogs, EB1089 or ILX-23-7553, prior to radiation was found to change the response to irradiation from growth arrest to cell death. [2][3][4][5] Our studies further excluded apoptosis and mitotic catastrophe as the modes of cell death when EB1089 was combined with radiation and were consistent with cell death occurring through autophagy. 2,3 Autophagy reflects a cellular response to stress in which the fusion of autophagosomes and lysosomes allows the degradation of subcellular organelles to generate energy and metabolic precursors; autophagy may be cytoprotective or cytotoxic, depending on the cells and the nature of the stressful challenge.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…2,17 In contrast, treatment with the vitamin D analogs, EB1089 or ILX-23-7553, prior to radiation was found to change the response to irradiation from growth arrest to cell death. [2][3][4][5] Our studies further excluded apoptosis and mitotic catastrophe as the modes of cell death when EB1089 was combined with radiation and were consistent with cell death occurring through autophagy. 2,3 Autophagy reflects a cellular response to stress in which the fusion of autophagosomes and lysosomes allows the degradation of subcellular organelles to generate energy and metabolic precursors; autophagy may be cytoprotective or cytotoxic, depending on the cells and the nature of the stressful challenge.…”
Section: Introductionsupporting
confidence: 58%
“…1 Although strategies have been developed in efforts to enhance the response to chemotherapy and radiation by interfering with cytoprotective signaling, there have been few direct attempts to address the problem of disease recurrence. One promising approach based on our previous work [2][3][4][5] may be to utilize vitamin D 3 or its analogs in combination with conventional therapies. 1,25D 3 , a steroid hormone with a central role in regulating calcium homeostasis, has been shown to produce pronounced effects on cell growth, differentiation and survival.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DeMasters et al showed an autophagic cell death response in irradiated MCF-7 and MCF-7/ caspase-3 breast tumor cells, an effect that was intensified by the vitamin D3 analogue EB 1089. 80 In the same study it was observed that the percentage of cells undergoing mitotic catastrophe and apoptosis was a small fraction of the overall cell population, while over 50% of the cells had increased presence of acidic vesicular organells. Similarly, Paglin et al showed that 48 hours after radiation with 10 Gy, autophagic vacuoles were present in 76% of the MCF-7 cells.…”
Section: B I O S C I E N C E D O N O T D I S T R I B U T Ementioning
confidence: 91%